Tamoanchán. Estudio arqueológico e histórico. - Henning, Paul; Plancarte, Francisco; Robelo, Cecilio A.; González, Pedro (Anales del Instituto Nacional de Antropología e Historia, 1912)
No se cuenta con resumen